Pengaruh Reward Sticker Picture terhadap Kedisiplinan Anak dalam Belajar di PAUD Tunas Kuala Kecamatan Medan Johor Tahun Ajaran 2020-2021 - Evy Suriani; Darajat Rangkuti; Dewi Fitria (Education & Learning, 2021)
The formulation of the problem in this study is whether there is an effect of reward sticker picture on discipline in learning in children at PAUD Tunas Kuala, Medan Johor District?. The type used in this study is the pre-experimental method and the research design used in this study is the one group pretest posttest design. The population in this study were all children in Group B at PAUD Tunas Kuala for the 2020-2021 academic year, consisting of the blue group and the red group, totaling 30 children. The sample in this study was the children of group B class Blue, totaling 15 children consisting of 9 girls and 6 boys. Data collection tools and techniques used are observation and documentation. Based on the results of the study, the average value of the pre-test of child discipline was 60.4 and the average value of the post-test of child discipline was 79.2. Based on the results of the t test, the value of tcount > ttable is (11.65 > 2.144). Then it can be stated that H0 is rejected and Ha is accepted, which means that there is an effect of reward sticker picture on children's discipline in learning at PAUD Tunas Kuala, Medan Johor Subdistrict for the 2020-2021 Academic Year. Thus, the hypothesis proposed that there is an effect of reward sticker picture on children's discipline in learning at PAUD Tunas Kuala Medan Johor District can be accepted as true.